The role of protective genetic variants in modulating epigenetic aging - Yosra Bejaoui (8552574) (2025)
Several progeroid syndromes’ causative mutations have been linked to epigenetic age acceleration as measured via several epigenetic clocks. At the same time, several protective variants have also been discovered that can reduce the risk of developing certain age-related disorders. However, the impact of these protective variants on epigenetic aging has not been well elucidated. Our research, which involved screening over 14,669 healthy individuals enrolled in the Qatar BioBank (QBB) and sequenced by the Qatar Genome Project (QGP), identified individuals carrying protective variants against age-related disorders, including Alzheimer’s disease (AD), type 2 diabetes (T2D), and atherosclerosis. In this study, we measured methylation levels in blood DNA using the EPIC v2 arrays. In addition, epigenetic age was calculated using various epigenetic clocks. Our analysis revealed that the APOE*E2 protective variant reduces the rate of GrimAge epigenetic aging when compared to individuals with the APOE4 AD risk allele. Furthermore, our differential DNA methylation analysis discovered the association of the PCSK9 protective variant with specific biological processes related to immune function and the cardiovascular system. In conclusion, APOE*E2 protective variants have a positive impact on epigenetic aging, while PCSK9 protective variants have a significant effect on DNA methylation signatures. Further studies are needed to better understand the underlying mechanisms by which protective variants influence epigenetic aging, particularly the role of APOE*E2 protective variants in biological aging. Furthermore, additional research is required to fully uncover the processes that might enable specific targeted therapies to mimic the effects of beneficial mutations, such as LOF variants in PCSK9, in reducing the risk of geriatric disorders. Other Information Published in: GeroScience License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11357-025-01548-2